LIFE CYCLE COST ANALYSIS FOR THE YAW DAMPING SYSTEM OF A WARSHIP FROM A FINANCIAL VIEWPOINT - Celebi, Ugur Bugra; Bilgili, Levent; Yilmaz, Bilkutay (UNIV ZAGREB FAC MECHANICAL ENGINEERING & NAVAL ARCHITECTURE, 2019)
Life cycle assessment (LCA) is implemented to various processes with a strict exception for naval platforms and warships. Thus, the recent studies for life cycle analysis of military ships are limited. LCA is a holistic method based on developing an optimization between environmental performance, cost-benefit balance and usability. LCC is a supporting subsection of LCA implemented to the analysis in order to calculate the probable costs during whole phases of a product. In this study, LCA and LCC are implemented to a naval platform and a calculation, which is based on escalation, is realized to compare the maintenance costs and initial cost for all life cycle of the platform. A generic warship is selected and yaw damping system of the ship was chosen for implementation of LCA and LCC. It is accepted that the systems and devices are used 1500 hours during cruising and 7260 hours during hoteling. First, the initial cost of yaw damping system is calculated, then, costs of long term maintenance with and without escalation are considered. In the final part, the profit gained by recycling of yaw damping system is calculated. The results has shown that an extra cost of 38 % and 19 % for operation and maintenance and total cost, respectively, must be added according to escalation calculations. While initial cost and operation and maintenance costs have 51 % and 49 % of total costs without escalation, the share of initial cost decreases to 43 % and the share of operation and maintenance increases to 57 % with the utilization of escalation.
Keywords: life cycle assessment; life cycle cost; naval platforms; recycle; escalation; ENVIRONMENTAL IMPACTS; LCA; IMPLEMENTATION; PERSPECTIVE; EMISSIONS; Engineering